Analisis Manajemen Hasil Pengolahan Kerupuk Udang Kayu Api Cempaka 2 di Mendahara Ilir Muara Sabak Jambi - Ambok Pangiuk (Indonesian Journal of Islamic Economics and Business, 2020)
The background of this study is that there are many people who produce Kayu Api shrimp crackers, so there are also many brands that have born in Mendahara Ilir Village, but from all brands, there is only one that is most highlighted and favored by customers namely Kayu Api Cempaka 2. This type of research is qualitative research by conducting interviews, observation, and documentation. It's used purposive sampling which the housewives who produce Kayu Api shrimp crackers are the samples. The objects of the research are house production of Kayu Api Cempaka 2 shrimp crackers and the place where the product is deposited in Mendahara Ilir Village and the implementation of production and Marketing of Kayu Api Cempaka shrimp crackers 2. The results show that, in production, they always maintain the taste quality of the shrimp so that they can maintain sustainable customers. From the marketing side, they use word-of-mouth promotion until they promote through social media such as Whatsapp and Facebook so that the product can be marketed outside of the village. For the supporting factors of the Kayu Api Cempaka 2 shrimp cracker business, there is assistance from the family as well as the presence of shops that are willing to entrust the Kayu Api Cempaka 2 shrimp crackers. Meanwhile, the inhibiting factor in the Kayu Api Cempaka 2 shrimp cracker business is capital and raw material such as fresh shrimp which really depends on the sailor.